Analysis of the User Satisfaction Level of the Flip Application Using the Pieces Method - Rama Dhio Putra Anugrah; Anggraeni Ridwan (Jurnal Indonesia Sosial Teknologi, 2024)
Interbank transfer transactions using third-party applications have become a common trend. The relatively high administrative fees for interbank transfers are the reason why people are switching to the Flip application. Flip is an application for transferring money between banks without admin fees. To measure the level of user satisfaction with the Flip application, a satisfaction analysis study was conducted using the PIECES method. The domains to be measured include Performance, Information, Economics, Control, Efficiency, and Service. The data used is the result of questionnaire responses from 100 respondents distributed using Google Forms, with data collection starting from April 28, 2024, to May 11, 2024. The analysis results showed a confidence level in the Flip application of 90%. The analysis and measurement results indicate that customers are very satisfied with the domains of performance, information, economics, control, efficiency, and service.